Centromeres Off the Hook: Massive Changes in Centromere Size and Structure Following Duplication of CenH3 Gene in Fabeae Species - Neumann, Pavel; Pavlíková, Zuzana; Koblížková, Andrea; Fuková, Iva; Jedličková, Veronika; Novák, Petr; Macas, Jiří (Molecular biology and evolution, 2015)
In most eukaryotes, centromere is determined by the presence of the centromere-specific histone variant CenH3. Two types of chromosome morphology are generally recognized with respect to centromere organization. Monocentric chromosomes possess a single CenH3-containing domain in primary constriction, whereas holocentric chromosomes lack the primary constriction and display dispersed distribution of CenH3. Recently, metapolycentric chromosomes have been reported in Pisum sativum, representing an intermediate type of centromere organization characterized by multiple CenH3-containing domains distributed across large parts of chromosomes that still form a single constriction. In this work, we show that this type of centromere is also found in other Pisum and closely related Lathyrus species, whereas Vicia and Lens genera, which belong to the same legume tribe Fabeae, possess only monocentric chromosomes. We observed extensive variability in the size of primary constriction and the arrangement of CenH3 domains both between and within individual Pisum and Lathyrus species, with no obvious correlation to genome or chromosome size. Search for CenH3 gene sequences revealed two paralogous variants, CenH3-1 and CenH3-2, which originated from a duplication event in the common ancestor of Fabeae species. The CenH3-1 gene was subsequently lost or silenced in the lineage leading to Vicia and Lens, whereas both genes are retained in Pisum and Lathyrus. Both of these genes appear to have evolved under purifying selection and produce functional CenH3 proteins which are fully colocalized. The findings described here provide the first evidence for a highly dynamic centromere structure within a group of closely related species, challenging previous concepts of centromere evolution.
Keywords: duplikace genu; sekvence nukleotidů; Genes, Plant; centromere drive; centromera; genetická variace; fylogeneze; Metaphase; gene duplication; Centromere; Phylogeny; molekulární sekvence - údaje; Amino Acid Sequence; adaptive evolution; centromere; molekulární evoluce; Evolution, Molecular; chromosome; Plant Proteins; chromozomy rostlin; Gene Duplication; Fabaceae; Chromosomes, Plant; chromatin; Selection, Genetic; CenH3; Chromatin; selekce (genetika); sekvence aminokyselin; metafáze; Molecular Sequence Data; Base Sequence; rostlinné geny; Genetic Variation; rostlinné proteiny